Immediate cytotoxicity of Chlamydia trachomatis for mouse peritoneal macrophages. - Kuo, C C (1978)
The toxicity of Chlamydia trachomatis was studied with mouse peritoneal macrophage culture. Inoculation of 30 inclusion-forming units of trachoma B/TW-5/OT organisms and 250 inclusion-forming units of lymphogranuloma venereum L2/434/Bu organisms per cell caused immediated toxicity, with the killing of 40 to 90% of the macrophages within 6 h after inoculation. Inhibition of phagocytosis by adsorption at 0 degrees C or by NaF pretreatment of macrophages prevented the toxicity, indicating that chlamydiae must be phagocytized to induce toxicity. Infectivity and toxicity could be dissociated, since ultraviolet-inactivated chlamydiae were still toxic. However, the toxicity was destroyed by heating the organisms at 56 degrees C for 10 min. Tetracycline, and antichlamydial drug, did not prevent toxicity, indicating that multiplication of the organisms was not required to induce toxicity. Toxicity was not prevented by treatment of macrophages with hydrocortisone. The toxicity of trachoma TW-5 was reduced by the rabbit immune serum of trachoma TW-5 but not by the rabbit immune serum of psittacosis meningopneumonitis.